Factor Affecting Work Morale of Nongkhaem District Office, Bangkok - Noijak, Rungrawee; Noppanatwongsakorn, Rachen (Journal of Graduate MCU KhonKaen Campus, 2025)
The purpose of this research is to study 1) The level of satisfaction with gifts and morale in the performance of personnel at Nong Kham District Office, Bangkok. 2) Personal factors affecting the morale and motivation of personnel at Nong Kham District Office, Bangkok. The research tool used was a questionnaire, with data collected from a total of 259 personnel at the Nong Kham District Office. The statistical methods used in the research for data analysis included percentage, mean, standard deviation, Independent Sample t-test, and comparing the relationships of sample groups greater than 2 groups using One-Way ANOVA. The research findings indicate that 1) The morale and motivation of the personnel at the Nong Kham District Office, Bangkok, are generally at a high level. When categorized by aspect, the area with the highest level of opinion regarding morale and motivation is the relationships with colleagues and subordinates, followed by the work environment, opportunities for advancement, job characteristics, policies and administration, and compensation and benefits, respectively. 2) The study of personal factors shows that they impact the morale and motivation of the personnel at the Nong Kham District Office, Bangkok. The characteristics of personal data such as gender, age, length of service, and average monthly income of the personnel at the Nong Kham District Office, Bangkok, were found to have no effect on the differences in morale and motivation. When categorized by aspect, it was found that personnel at the Nong Kham District Office, Bangkok, with different average monthly incomes have a significant impact on morale and motivation in terms of job characteristics, with a statistically significant difference at the 0.05 level.